Incidence of Pulmonary Vein Stenosis in Patients Submitted to Atrial Fibrillation Ablation: A Comparison of the Selective Segmental Ostial Ablation vs the Circumferential Pulmonary Veins Ablation - Tamborero, David; Mont, Lluis; Nava, Santiago; de Caralt, Teresa M.; Molina, Irma; Scalise, Andrea; Perea, Rosario J.; Bartholomay, Eduardo; Berruezo, Antonio; Matiello, Maria; Brugada, Josep (Journal of interventional cardiac electrophysiology, 2005)
Pulmonary vein (PV) stenosis is an important complication of the AF ablation and could be underestimated if their assessment is not systematically done. Selective Segmental Ostial Ablation (SSOA) and Circunferential Pulmonary Veins Ablation (CPVA) have demonstrated efficacy in atrial fibrillation (AF) treatment. In this study the real incidence of PV stenosis in patients (pts) submitted to both SSOA and CPVA was compared. Those pts with focal activity and normal left atrial size were submitted to SSOA, remaining pts were submitted to CPVA to treat refractory, symptomatic AF. Contrast enhanced magnetic resonance angiography (MRA) was routinely performed in all patients 4 months after the procedure. A series of 73 consecutive patients (mean age of 51 +/- 11 years; 75% male) were included. SSOA was performed in 32 patients, and the remaining 41 patients underwent to CPVA, obtaining similar efficacy rates (72% vs 76% arrythmia free probability at 12 months; log rank test p = NS). Six patients had a significant PV stenosis, all in SSOA group none in CPVA group (18.8% vs 0%; p = 0.005). All patients were asymptomatic and the stenosis was detected in routine MRA. No predictors of stenosis has been identified analysing patient procedure characteristics. PV stenosis is a potential complication of SSOA not seen in CPVA. The study confirms than MRA is useful for identifying patients with asymptomatic PV stenosis.